Cyber-Attacks and Cryptocurrencies - Guglielmo Maria Caporale; Woo-Young Kang; Fabio Spagnolo; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper provides some comprehensive evidence on the effects of cyber-attacks on the returns, realized volatility and trading volume of five of the main cryptocurrencies (Bitcoin, Ethereum, Litecoin, XRP and Stellar) in 99 developed and developing countries. More specifically, it investigates the effects of four different types of cyber-attacks (cyber-crime, cyber-espionage, hacktivism and cyber-warfare) on four target sectors (government, industry, finance and cryptocurrency exchange). We find that in the US cyber security firms tend to overreact to cyberattacks affecting cryptocurrencies and more wealth is spent on cyber security compared to other countries. Both hacktivism and cyber-warfare have a significant impact on cryptocurrencies. Cryptocurrency exchanges are more vulnerable to cyber-attacks in non-US countries and in the presence of high economic uncertainty and less so if the industry sector is already being targeted. Finally, cryptocurrency investors exhibit risk-loving behaviour when the hash rate and cryptocurrency returns increase and risk-averse one when cyber-attacks target the financial and industry sectors and economic uncertainty is high.
Keywords: C22; E40; G10; 330; cyber security; cyber-attacks; cryptocurrencies; return and volatility jumps